2006
DOI: 10.1364/oe.14.005411
|View full text |Cite
|
Sign up to set email alerts
|

Deviations of Lambert-Beer’s law affect corneal refractive parameters after refractive surgery

Abstract: We calculate whether deviations of Lambert-Beer's law, which regulates depth ablation during corneal ablation, significantly influence corneal refractive parameters after refractive surgery and whether they influence visual performance. For this, we compute a point-to-point correction on the cornea while assuming a non-linear (including a quadratic term) fit for depth ablation. Post-surgical equations for refractive parameters using a non-linear fit show significant differences with respect to parameters obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Therefore, the different ablation profiles of transition zone must be designed for hyperopic and myopic correction. On the other hand, the increase of the postoperative corneal asphericity and induction of spherical aberration could be explained partly by the ablation efficiency reduction due to laser oblique incidence [24]- [28]. Also, our previous results indicated that the effect of laser oblique incidence exerted an important influence on the residual wavefront aberrations [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the different ablation profiles of transition zone must be designed for hyperopic and myopic correction. On the other hand, the increase of the postoperative corneal asphericity and induction of spherical aberration could be explained partly by the ablation efficiency reduction due to laser oblique incidence [24]- [28]. Also, our previous results indicated that the effect of laser oblique incidence exerted an important influence on the residual wavefront aberrations [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential variables that influence corneal ablation such as the physical aspects of ablation, biomechanical effects [1,[32][33][34] and different transition zones [35] were not considered. Analyzing Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many theoretical and experimental studies on visual quality after corneal refractive surgery, most refer to myopia [1][2][3][4][5][6][7][8][9][10] while fewer examine hyperopia [11][12][13][14][15][16]. As in myopia [1,6,7,10], experimental results on hyperopic correction show a decline in best-corrected visual quality after corneal surgery, with a post-surgical increase in corneal and total aberrations [13,14] as well as a deterioration in contrast sensitivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of factors influence the laser ablation and outcome. Among them, laser energy delivery technique [6,7], ablation decentration and registration [8,9], eye tracking [10,11], flap [12], physical characteristics of ablation [13][14][15][16][17][18][19], wound-healing and biomechanics of the cornea [20][21][22][23][24], have been explored to predict or explain the clinically observed discrepancy between intended and actual outcomes. The quantification of influence of these factors is important for providing the optimal outcome for the refractive surgeries.…”
Section: Introductionmentioning
confidence: 99%